POTENTIAL ANALYSIS AND DEVELOPMENT PLAN TOURIS OBJECT BANYIS WATERFALL IN THE VILLAGE OF THE WORKS COMPETITION OF LEDO DISTRICT BENGKAYAANG DISTRICT - Wahab Wahab (Cross-Border Journal of Business Management, 2021)
The tourism sector is one of the people's economic potentials that needs to be developed in order to improve community welfare and regional development. This is done thoroughly and evenly so that there is a need for directed and coordinated development. In addition, the concept of tourism includes empowerment efforts, tourism businesses, tourist objects and attractions and various types of tourism businesses. The waterfall which is a tourist attraction is one of the promising economic industrial activities, the existence of a tourist attraction also has an impact on the economy of the surrounding community, with the existence of a tourist attraction in an area with good management it will indirectly open up jobs for the surrounding community in particular. This research, including qualitative research, the data used in the form of primary data which is the result of interviews and observations. Data processing is carried out using Data Reduction techniques, namely summarizing or sorting out the main things, focusing on important things, looking for themes and patterns and removing unnecessary ones, then carrying out the data presentation stage, so that verification can be carried out in the form of a review of the notes. - Record the data obtained. The Banyis Waterfall Tourism Object will provide good potential to be developed and will provide benefits for the people of the Karya Competition Village. However, the lack of public understanding about the development of the Banyis Waterfall tourist attraction will result in not achieving the effectiveness of the planned waterfall tourism development. So it is very necessary for the contributions of related parties in the potential development plan that has been owned by the Village of Karya Competition, especially the potential of Banyis Waterfall.